5a-(8-a)=4a-10

Simplify each term.

Apply the distributive property.

5a-1⋅8–a=4a-10

Multiply -1 by 8.

5a-8–a=4a-10

Multiply –a.

Multiply -1 by -1.

5a-8+1a=4a-10

Multiply a by 1.

5a-8+a=4a-10

5a-8+a=4a-10

5a-8+a=4a-10

Add 5a and a.

6a-8=4a-10

6a-8=4a-10

Subtract 4a from both sides of the equation.

6a-8-4a=-10

Subtract 4a from 6a.

2a-8=-10

2a-8=-10

Add 8 to both sides of the equation.

2a=-10+8

Add -10 and 8.

2a=-2

2a=-2

Divide each term in 2a=-2 by 2.

2a2=-22

Cancel the common factor of 2.

Cancel the common factor.

2a2=-22

Divide a by 1.

a=-22

a=-22

Divide -2 by 2.

a=-1

a=-1

Solve for a 5a-(8-a)=4a-10